An insight into the sialome of blood feeding Nematocera - Ribeiro, José M.C. (2010)
Within the Diptera and outside the suborder Brachycera, the blood feeding habit occurred at least twice, producing the present day sand flies, and the Culicomorpha, including the mosquitoes (Culicidae), black flies (Simulidae), biting midges (Ceratopogonidae) and frog feeding flies (Corethrellidae). Alternatives to this scenario are also discussed. Successful blood feeding requires adaptations to antagonize the vertebrate's mechanisms of blood clotting, platelet aggregation, vasoconstriction, pain and itching, which are triggered by tissue destruction and immune reactions to insect products. Saliva of these insects provides a complex pharmacological armamentarium to block these vertebrate reactions. With the advent of transcriptomics, the sialomes (from the Greek word sialo=saliva) of at least two species of each of these families have been studied (except for the frog feeders), allowing an insight into the diverse pathways leading to today's salivary composition within the Culicomorpha, having the sand flies as an outgroup. This review catalogs 1,288 salivary proteins in 10 generic classes comprising over 150 different protein families, most of which we have no functional knowledge. These proteins and many sequence comparisons are displayed in a hyperlinked spreadsheet that hopefully will stimulate and facilitate the task of functional characterization of these proteins, and their possible use as novel pharmacological agents and epidemiological markers of insect vector exposure.